Rumen Parameters of West African Dwarf Sheep Fed Panicum maximum Supplemented with Varying Levels of Gmelina Arborea Leaves - Binuomote, R. T; Muftaudeen, N.; Adekunle, C.A. (Animal Health Journal, 2022)
Purpose: This experiment was carried out to assess the rumen characteristics of West African dwarf sheep fed varying level of Panicum maximum supplemented with Gmelina arborea leaves. Methodology: Twenty (20) healthy West African Dwarf sheep with average weight of 10+0.55kg and were randomly allotted to five (5) diet with four (4) animals per treatment in a completely randomized design. The diets compared were A (100% Panicum maximum); B (75% Panicum maximum + 25% Gmelina arborea leaf); C (50% Panicum maximum + 50% Gmelina arborea leaf); D (25% Panicum maximum + 75% Gmelina arborea leaf); and E (100% Dried Gmelina arborea leaf). The diet samples were analyzed for chemical composition and anti-nutritive components. At the end of feeding trial, rumen liquor from the experimental animals were collected for rumen fermentation characteristics Data were collected on volatile fatty acids (VFAs) production rumen pH and ammonia nitrogen. .Findings: The results obtained showed that the chemical composition and the anti-nutrient content in the diets were significantly (P<0.05) different. Dry matter was highest in diet E (82.50%) and lowest in diet A (36.50%). The crude protein ranged between (9.75%) in diet A and (18.33%) in diet E. the Neutral detergent fibre, Acid detergent fibre and Acid detergent lignin was highest in diet B (63.30%), A (31.50%) and C (16.60%) respectively. the anti-nutrient content of the diet showed no any negative effect on the animals. The acetic acid (5.93%), propionic acid (5.65%), butyric acid (5.40%), valeric acid (5.37%), total volatile fatty acids (34.37mmol/liter), lactic acid (7.37%) and pH (8.25) of the rumen were significantly (p<0.05) higher in animals on diet B than those on diets A, C, D and E. Animals on diet D had the highest values in terms of rumen ammonia concentration (0.53mg/100ml) followed closely was diet C and E with the value (0.48mg/100ml). Uique contribution to theory, practice and policy: It can be concluded that feeding West African Dwarf (WAD) sheep with Panicum maximum supplemented with Gmelina arborea leaves offers potential results in supplying fermentable nutrients needed to enhance favourable rumen environment for effective microbial activities without any adverse effect on on the rumen parameters status of the animals.